Peningkatan Hasil Belajar Peserta Didik Melalui Penerapan Model Snowball Throwing Mata Pelajaran Bahasa Indonesia Kelas V SDN-4 Kasongan Lama Tahun Pelajaran 2016/2017 - Widia Alfisa; Bulkani Bulkani (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study aims: (1) To find out the learning activities of Indonesian Language students in class V by applying the Snowball Throwing learning model. (2) To find out the improvement of Indonesian language learning outcomes of fifth-grade students of Kasongan Lama Elementary School-4 by asking the Snowball Throwing learning model. The type in this study used a variety of classroom action research (CAR). As for the subjects in this study were students of class V SDN-4 Kasongan Lama, amounting to 24 students. The instruments used in this study were observation sheets and test questions about learning outcomes in the form of essays. The data analysis technique used is qualitative and quantitative.